2018
DOI: 10.1111/sji.12728
|View full text |Cite
|
Sign up to set email alerts
|

LprG and PE_PGRS33 Mycobacterium tuberculosis virulence factors induce differential mitochondrial dynamics in macrophages

Abstract: The interaction of a pathogen with its host cell takes place at different levels, including the bioenergetics adaptation of both the pathogen and the host cell in the course of an infection. In this regard, Mycobacterium tuberculosis infection of macrophages induces mitochondrial membrane potential (Δψm) changes and cytochrome c release, depending on the bacteria strain's virulence, and the mitochondrial dynamics is modified by pathogens, such as Listeria monocytogenes. Here, we investigated whether two M. tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…Mtb Rv1411c (LprG/p27) induces mitochondrial fission and changes mitochondrial Ca 2+ dynamics and lowers the host rate of respiration (Path F, Figure 2 ). On the contrary, Rv1818c (PE_PGRS33) promotes mitochondrial fusion with no effect on Ca 2+ uptake and respiratory rate of the cell (Aguilar-López et al, 2019 ). Similar effects were observed upon infection with M. smegmatis overexpressing MAV2054 in bone marrow-derived macrophages.…”
Section: Mycobacterium Tuberculosis Infection Reallocates MImentioning
confidence: 99%
“…Mtb Rv1411c (LprG/p27) induces mitochondrial fission and changes mitochondrial Ca 2+ dynamics and lowers the host rate of respiration (Path F, Figure 2 ). On the contrary, Rv1818c (PE_PGRS33) promotes mitochondrial fusion with no effect on Ca 2+ uptake and respiratory rate of the cell (Aguilar-López et al, 2019 ). Similar effects were observed upon infection with M. smegmatis overexpressing MAV2054 in bone marrow-derived macrophages.…”
Section: Mycobacterium Tuberculosis Infection Reallocates MImentioning
confidence: 99%
“…It has been proved that LprG involved in triacylglyceride levels, growth rate, and virulence regulation (35). Its implication in mycobacterium virulence has been appeared through the induction of mitochondrial ssion, interference with complex I and complex II respiration, and modi cation of mitochondrial calcium uptake, which in turn proposing that LprG-stimulated cells are in a lower bioenergetics state, which could support its immunosuppressive capacity in infection (36). The identi cation of LprG protein in M. tuberculosis was previously con rmed as P27 in the Mycobacterium tuberculosis complex and its gene is conserved across several pathogenic and nonpathogenic Mycobacterium species (37).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of mitochondrial dynamics during Mtb infection has been recently recognized (12)(13)(14)(15). However, its role in bactericidal activity and underlying mechanism remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…However, how Mtb infection influences mitochondrial dynamics and the metabolic profile remains uncertain. A previous study found that different Mtb virulent factors altered differential mitochondrial dynamics in macrophages (12). Jamwal et al (2012) showed that, compared with an avirulent strain, a virulent strain of Mtb elongated the mitochondria and increased ATP levels in a human macrophage THP-1 cell line as a way to prevent host macrophage apoptosis (13).…”
Section: Introductionmentioning
confidence: 99%